Pengaruh Celebrity Endorser, Brand Image, Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Produk Kosmetik Wardah (Studi Kasus Pada Mahasiswi Fakultas Ekonomi dan Bisnis Universitas Islam Malang Angkatan 2019) - Nila Kusumawati; Siti Asiyah; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this study is to determine and analyze the Influence of Celebrity Endorsers, Brand Image and Product Quality on Purchasing Decisions on Wardah Cosmetic Products (Case Study on Students of the Faculty of Economics and Business, Islamic University of Malang, Class of 2019). This study used quantitative research methods using questionnaires with a Likert scale of 1-5. The population in this study was female students who had bought and used Wardah cosmetic products. The data collection technique uses nonprobability sampling, namely by purposive sampling techniques. The sample in this study amounted to 65 respondents. Data analysis techniques use research instrument tests, classical assumption tests, multiple regression analysis tests, f tests and t tests and determination coefficient tests. As data collection material analyzed with the help of IBL SPSS Statistics software. The results of this study show that celebrity endorsers have a significant effect on purchasing decisions, brand image has a significant effect on purchasing decisions and product quality has a significant effect on purchasing decisions. Keywords: Celebrity Endorser, Brand Image, Product Quality, and Purchasing Decision.